Pengaruh Viral Marketing pada Sosial Media Terhadap Keputusan Pembelian Pelanggan dengan Brand Awareness sebagai Variabel Intervening - Adila Khairunnisa Khansa; Ibnu Khajar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of viral marketing on social media on customer purchasing decisions with brand awareness as an intervening variable in Wedhang Jahe Powder Cap Bima Micro, Small and Medium Enterprises (MSMEs). In the digital era and after the COVID-19 pandemic, digitalization has accelerated changes in consumer behavior, encouraging MSME players to optimize online marketing strategies, including viral marketing. This study uses a quantitative approach with a survey method through questionnaires to consumers of Wedhang Jahe Cap Bima products. Data were analyzed using inferential statistical techniques, including validity, reliability, and path analysis to test the mediating role of brand awareness. The results of the study are expected to show that viral marketing has a significant effect on brand awareness, and brand awareness positively mediates this influence on purchasing decisions. The findings provide theoretical contributions to the study of digital marketing as well as practical implications for the development of social media-based MSME promotion strategies to increase brand awareness and purchase intentions